Mountains : mapping the earth's extremes - Dech, Stefan; Messner, Reinhold (New York Thames & Hudson Inc, 2016)
This thrilling combination of science, history, geography and adventure brings together more than 170 breath-taking virtual images of mountains, created using modern satellite technology with unprecedented precision and detail, allowing viewpoints that have never before been possible; the history of mountaineering, retold by world-class adventurer Reinhold Messner; first-hand accounts of expeditions by great climbers.